Hubungan Antara Celebrity Endorser pada Konten Tiktok Endorsement dengan Minat Berkunjung Followers ke Jatinangor Coffee House. - Muhammad Abdul Ghany; Dede Lilis (UNISBA Press, 2024)
Absract. The Celebrity endorser phenomenon on TiktokEndorsement content has now become one way to disseminate information in the era digital or social media. The same thing is done by Jatinangor Coffee House in collaboration with Celebrity Endorser whose account is called @Trisahanjani. The importance of this collaboration is to influence consumers interest in visiting Jatinangor Coffee House so that the JatinangorCoffee House brand become known to the wider community or social media users which can make Jatinangor Coffee House become more developed with its branch outlets spread throughout cities in Indonesia. The porpose of this research is to find out how strong the relationship is between Celebrity Endorsers on TiktokEndorsement Content and Followers interest in visiting Jatinangor Coffee House. Using the SOR theory or (Stimulus Organism Response) which is used to influence the stimulus (stimulus) captured by the consumers five senses (organism) and then perceived, resulting in a response. The use of Celebrity Endorser communicator services that have characteristics will influence attitudes or positive consumer responses towards the product, so that consumers will consider it in the purchasing process and it is hoped that this will directly influence behavior through the subconscious. Interst in visiting is basically a feeling of wanting to visit a place that is interesting to visit. The research uses a quantitative type of research with a correlational study with a technique for determining sample collection using the Slovin formula with a population of 3.648 and there are 100 samples using a simple random sampling technique which is random without paying attention to the strata in the population. The instrument testing, while the data analysis technique uses descriptive tests. The results of this study show that there is a strong relationship between Celebrity Endorsers in terms of trustworthiness and interest in visiting, there is a strong relationship between Celebrity Endorsers in attractiveness and interest in visiting, and there is a strong relationship between Celebrity Endorsers in expertise (expertise) with an interest in visiting. So it can be concluded that there is a strong relationship between Celebrity Endorsers on Tiktok endorsement content and followers interest in visiting Jatinangor Coffee House. Abstrak. Fenomena endorser selebriti di TikTok telah merevolusi cara informasi disebarkan di era media digital dan sosial. Jatinangor Coffee House telah memanfaatkan tren ini melalui kolaborasi dengan endorser selebriti @Trisahanjani. Kerjasama ini bertujuan untuk memengaruhi minat konsumen dalam mengunjungi Jatinangor Coffee House, sehingga meningkatkan visibilitas mereknya dan memperluas jangkauannya di seluruh Indonesia.Penelitian ini bertujuan untuk menilai hubungan antara endorser selebriti di TikTok dan minat pengikut dalam mengunjungi Jatinangor Coffee House, dengan menggunakan teori SOR (Stimulus Organism Response). Teori ini menyatakan bahwa stimuli yang dipersepsikan melalui indera menghasilkan respons. Endorser selebriti, dengan kemampuan komunikatif dan karakteristik menarik mereka, diyakini dapat membentuk sikap positif terhadap produk, sehingga memengaruhi perilaku konsumen secara tak sadar.Penelitian kuantitatif ini, dengan analisis korelasional, melibatkan 100 sampel yang dipilih secara acak dari populasi 3.648 menggunakan rumus Slovin. Studi ini mengungkapkan korelasi signifikan antara kepercayaan, daya tarik, dan keahlian endorser selebriti dengan minat pengikut dalam mengunjungi Jatinangor Coffee House. Akibatnya, disimpulkan bahwa konten endorser TikTok secara signifikan memengaruhi keinginan pengikut untuk mengunjungi Jatinangor Coffee House, menunjukkan strategi pemasaran yang efektif untuk pertumbuhan dan jangkauan merek tersebut.